Provenance and paleoclimatic implications of loess deposits in Shandong Province, eastern China. (September 2021) - Wang, Yongda; Yang, Shiling; Ding, Zhongli
Abstract: The loess deposits in Shandong Province in eastern China potentially provide valuable insights into past environmental changes. However, their precise provenance and paleoclimatic implications are unclear. We studied three loess sections located in the piedmont of the Central Shandong Mountains (PCSM) and in an offshore island in Bohai Gulf. Both the glacial loess and interglacial paleosol units are characterized by a coarse grain size, indicating a proximal sediment source. Using the "grain size–transport distance" model established for the Chinese Loess Plateau (CLP), the estimated source-sink distance is 200–300 km for the PCSM loess and 100–200 km for the coastal loess. This suggests that fluvial deposits of the Yellow River system in the North China Plain and sediments on the adjacent continental shelf are the major provenance for the Shandong loess. In contrast to the CLP, the Shandong loess does not show a consistent pattern of coarse grain size and low magnetic susceptibility values in glacial loess compared with interglacial paleosols, likely due to frequent changes in dust sources caused by diversions of the Yellow River and local hydroclimatic conditions. Nevertheless, the loess-paleosol alternations in the Shandong loess are a product of global glacial–interglacial cycles.